2013
DOI: 10.1002/chem.201301510
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol‐/Estradiol‐Appended Alkynylplatinum(II) Complexes as Supramolecular Gelators: Synthesis, Characterization, Photophysical and Gelation Studies

Abstract: A series of cholesterol-/estradiol-appended alkynylplatinum(II) complexes with tridentate N-donor ligands, based on 2,6-bis(1-alkylpyrazol-3-yl)pyridine, has been synthesized and characterized by (1)H NMR spectroscopy, FAB-mass spectrometry, and elemental analysis. Their photophysical properties have also been investigated. Computational studies have been performed to provide insights into the nature of the electronic transitions. Some of the complexes have been found to form stable thermo- and mechanoresponsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…To date, it has been reported that, in either organic or aqueous media, luminescent Pt(II) complexes are able to form homo- 82,83 and hetero-metallic [84][85][86] supramolecular architectures and superstructures such as nanowires, 87 nanosheets, nanowheels, nanotubes, 88 liquid crystals, 89 and metallogels 90,91 with very appealing (electro)optical, [92][93][94] sensing 95,96 and semiconducting properties. 97 Also, it has been nicely shown that the formation of such metallophilic interactions in luminescent square planar platinum complexes, and the subsequent modulation of their photophysical properties, can be induced by the presence of biologically relevant molecules and polyelectrolytes in aqueous media.…”
Section: Basic Photophysics Of D 8 Transition Metal Complexesmentioning
confidence: 99%
“…To date, it has been reported that, in either organic or aqueous media, luminescent Pt(II) complexes are able to form homo- 82,83 and hetero-metallic [84][85][86] supramolecular architectures and superstructures such as nanowires, 87 nanosheets, nanowheels, nanotubes, 88 liquid crystals, 89 and metallogels 90,91 with very appealing (electro)optical, [92][93][94] sensing 95,96 and semiconducting properties. 97 Also, it has been nicely shown that the formation of such metallophilic interactions in luminescent square planar platinum complexes, and the subsequent modulation of their photophysical properties, can be induced by the presence of biologically relevant molecules and polyelectrolytes in aqueous media.…”
Section: Basic Photophysics Of D 8 Transition Metal Complexesmentioning
confidence: 99%
“…With a similar structure, the complex 5a-5d showed thixotropic properties. 38 For example, shaking the gel of 5d (10 mg mL À1 in cyclohexane obtained by a heatingcooling process) with a vibrator for 5 min would disturb the gel completely, a state that would persist for half an hour, and the gel would then reform.…”
Section: Metallogelsmentioning
confidence: 99%
“…52,54 In this study, we report nucleoside based hydrogels showing metal ion dependent self-healing properties which is unprecedented. The use of metal ions in making supramolecular gels 50,55,[59][60][61][62][63][64][65][66][67][68][69][70] is a potent approach with unusual properties and most of the reported metallogels lack a deeper insight into the ne-tuning of gel properties by using different metal ions. Interestingly, in our study, most of the dG gels show an excellent thixotropic property whereas G gels lack such a property.…”
Section: Introductionmentioning
confidence: 99%